Peningkatan Pola Asuh Melalui Penyuluhan Gizi dan Kesehatan di Kelurahan Samaan, Kota Malang - Harini, Sri; Jannah, Akyunul; Mulyanto, Angga Dwi; Rahman, Hairur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Nutrition and health counseling in Samaan Village, Malang City, aims to increase parents' understanding of the importance of proper parenting in supporting child development, especially in the context of stunting prevention. Through a Participatory Action Research (PAR) approach, this activity involved posyandu cadres and the PKK mobilizing team in designing and implementing counseling. The materials presented focused on balanced nutrition, psychological stimulation, and the importance of routine health checks for toddlers. The results of the counseling showed an increase in parents' understanding of the importance of nutrition in supporting children's physical and cognitive development, as well as the application of better parenting.